EFFECTS OF LIGNITE PROPERTIES ON THE HYDROLIQUEFACTION BEHAVIOR OF REPRESENTATIVE TURKISH LIGNITES - ONER, M; BOLAT, E; DINCER, S (TAYLOR & FRANCIS INC, 1992)
The conversion and yield data obtained for hydroliquefaction of 11 different Turkish lignites in tetralin, anthracene, and creosote oils with or without catalyst at 440-degrees-C and 80 bar were correlated with the lignite properties obtained from proximate, ultimate, and petrographic analyses. The intercorrelation of experimental results and analytical data was evaluated by both simple linear regression and stepwise multiple linear regression analyses. Simple linear correlations between conversion and yield data with individual lignite parameters are unsatisfactory. An approach utilizing a stepwise multiple linear regression analysis led to a number of linear equations relating oil yields to ash, sulfur, volatile matter, elemental carbon, maceral, and xylene extract contents of the lignites.
Keywords: LIGNITE PROPERTIES; HYDROLIQUEFACTION; TURKISH LIGNITES; REGRESSION ANALYSIS; COAL-LIQUEFACTION BEHAVIOR; CATALYTIC ACTIVITY; MINERAL MATTER; DEPENDENCE; HYDROGENATION; REACTIVITY; Energy & Fuels; Engineering